Traditional and Non-Traditional Feeds in Poultry Feeding: A review - Basim Aboud Abbas (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
Quite a few nations have a thriving poultry feed sector. This essay focuses on Feed, which is regarded as the most expensive component of poultry production. Feed processing also raises the price of feed, in addition to the cost of ingredients. The population of the world is projected to rise to 9.1 billion people by the year 2050. Meat and egg consumption from chicken is rising worldwide, primarily in developing nations. As a result, there would be a rise in the demand for poultry feeds worldwide. Due to their significance in improving the general health of birds, additives in poultry feeding are nowadays a need in any product of factories making feedings. Nowadays, especially in emerging nations, the supply of feeds for chicken nutrition is becoming increasingly competitive. The use of alternative feedstuffs to replace soybean and yellow corn in poultry diets and the alternative feedstuffs that can be used in poultry feeds are both being pursued. Additionally, the availability of nutritional content and methods for enhancing the nutritive quality of such nontraditional feedstuffs.